Asphalt modifier, self-repairing asphalt as well as preparation method and application of self-repairing asphalt

By designing a hydrogen bond interface crosslinking between the soft and hard phases, the self-healing properties and high-temperature rutting resistance of asphalt are improved, solving the durability problem of asphalt pavement in extreme environments and achieving efficient self-healing and crack resistance, which is in line with the design of green and sustainable pavement materials.

CN120795421APending Publication Date: 2025-10-17CHONGQING JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511034010.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing asphalt pavements are prone to low-temperature cracking and high-temperature rutting under extreme environments and heavy traffic, making it difficult to maintain durability. Furthermore, traditional repair methods affect traffic and increase operation and maintenance costs.

Method used

An asphalt modifier comprising a soft phase and a hard phase is used. The soft phase consists of thioctic acid compounds, 1,3-dienylbenzene, iron halide, and natural polymer compounds, while the hard phase consists of epoxidized natural rubber, carboxyphenylboronic acid ester derivatives, 1,2-dialkylimidazole, alkylamidoacetic acid, and zinc alkylate. Self-assembly is achieved through hydrogen bonding interfacial crosslinking, thereby improving the self-healing and rutting resistance of asphalt.

Benefits of technology

It significantly improves the self-healing properties and high-temperature rutting resistance of asphalt, while also improving low-temperature crack resistance, reducing operation and maintenance costs, and meeting the design requirements of green and sustainable pavement materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005518163440000021
    Figure BDA0005518163440000021
  • Figure BDA0005518163440000031
    Figure BDA0005518163440000031
  • Figure BDA0005518163440000032
    Figure BDA0005518163440000032
Patent Text Reader

Abstract

The invention discloses an asphalt modifier, self-repairing asphalt as well as a preparation method and application of the self-repairing asphalt. The asphalt modifier comprises a soft phase and a hard phase, the soft phase is prepared from the following raw materials in parts by weight: 12 to 20 parts of a lipoic acid compound, 3 to 6 parts of 1, 3-dienylbenzene, 0.2 to 0.8 part of iron halide and 0.1 to 0.3 part of a natural high-molecular compound; the hard phase is prepared from the following raw materials in parts by weight: 20 to 30 parts of epoxidized natural rubber, 1 to 5 parts of derivatives of carboxyphenylboronic acid ester, 0.5 to 2 parts of 1, 2-dialkyl imidazole, 0.5 to 2 parts of alkyl amido acetic acid and 0.5 to 2 parts of alkyl acid zinc. The asphalt modifier provided by the invention can improve the low-temperature crack resistance, high-temperature rut resistance and self-repairing capability of asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a bitumen modifier, a self-repairing bitumen and a preparation method and use thereof. BACKGROUND

[0002] Polymer self-repairing bitumen occupies a dominant position in bitumen pavement paving technology due to its excellent road performance. However, under the long-term effect of extreme environment (such as low-temperature freeze-thaw and high-temperature rutting) and heavy traffic, the bitumen pavement is prone to low-temperature cracking and structural damage, which makes it difficult to maintain the durability of the bitumen pavement. The current common maintenance methods such as traditional repair and closed repair not only affect the normal operation of road traffic, but also significantly increase the operation and maintenance cost. Therefore, developing a new type of bitumen material with high toughness and self-repairing ability can prolong the service life of the pavement and reduce the operation and maintenance cost. Bitumen material has significant temperature sensitivity, which presents high brittleness at low temperature. Improving the low-temperature toughness of bitumen material has become an important direction of modification research. Improving the self-repairing ability of bitumen material and inhibiting the initiation and propagation of cracks are effective means to reduce the maintenance cost of bitumen pavement. Recent researches have shown that the use of polymers containing dynamic covalent bonds or non-covalent bonds can cause reversible exchange of molecular chains, and the unstable free radicals generated at the crack interface can drive rapid healing, which is an important mechanism to improve the self-repairing ability of materials. The stronger the driving ability of this mechanism at lower temperature, the more significant the self-repairing effect of the material. However, at the same time, the breaking of dynamic bonds will reduce the crosslinking density of the polymer, thereby causing the decrease of viscosity and weakening the high-temperature rutting resistance of bitumen. Therefore, it is urgent to develop a bitumen modifier that takes into account the self-repairing ability and high-temperature rutting resistance.

[0003] In summary, there is an urgent need for a bitumen modifier to ensure the low-temperature cracking resistance of bitumen material and improve its rutting resistance and self-repairing performance under high-temperature conditions. SUMMARY

[0004] An object of the present application is to provide a bitumen modifier. The bitumen modifier can improve the self-repairing performance of bitumen. Further, the bitumen modifier can improve the rutting resistance and low-temperature cracking resistance of bitumen under high-temperature conditions. Another object of the present application is to provide a preparation method of a bitumen modifier. Still another object of the present application is to provide a use of a bitumen modifier. Yet another object of the present application is to provide a self-repairing bitumen. The bitumen has good self-repairing performance, rutting resistance under high-temperature conditions and low-temperature cracking resistance. Yet another object of the present application is to provide a preparation method of a self-repairing bitumen.

[0005] The present application achieves the above objects by the following technical solutions.

[0006] In one aspect, according to the present application, a bitumen modifier is provided, comprising a soft phase and a hard phase;

[0007] wherein the soft phase is prepared from raw materials comprising 12 to 20 parts by weight of a lipoic acid compound, 3 to 6 parts by weight of 1,3-dienylbenzene, 0.2 to 0.8 parts by weight of iron halide, and 0.1 to 0.3 parts by weight of a natural polymer compound;

[0008] The lipoic acid compound is represented by formula (I):

[0009]

[0010] In formula (I), R is selected from substituted or unsubstituted amino, hydroxyl, substituted or unsubstituted C1-C5 alkoxy; preferably, R is selected from unsubstituted amino, hydroxyl, or unsubstituted C1-C5 alkoxy; more preferably, R is selected from unsubstituted amino, hydroxyl, or unsubstituted C1-C2 alkoxy. 10 The natural polymer compound is selected from one or more of starch, cellulose, chitosan, and lignin.

[0011] The hard phase is prepared from raw materials comprising 20 to 30 parts by weight of epoxidized natural rubber, 1 to 5 parts by weight of a carboxyphenylboronic acid ester derivative, 0.5 to 2 parts by weight of 1,2-dialkylimidazole, 0.5 to 2 parts by weight of alkylamidoacetic acid, and 0.5 to 2 parts by weight of zinc alkylate; the epoxidized natural rubber has an epoxide degree of 25 to 55%, and the carboxyphenylboronic acid ester derivative has a structure represented by formula (II):

[0012]

[0013] In formula (II), R1 is selected from hydrogen, halogen, C1-C5 alkyl. 10

[0014] The lipoic acid compound is used in an amount of 12 to 20 parts by weight; preferably, 14 to 18 parts by weight; more preferably, 15 to 17 parts by weight. According to certain embodiments of the present application, the lipoic acid compound is used in an amount of 16 parts by weight.

[0015] In the present application, the lipoic acid compound is represented by formula (I):

[0016]

[0017] In formula (I), R is selected from substituted or unsubstituted amino, hydroxyl, substituted or unsubstituted C1-C5 alkoxy; preferably, R is selected from unsubstituted amino, hydroxyl, or unsubstituted C1-C5 alkoxy; more preferably, R is selected from unsubstituted amino, hydroxyl, or unsubstituted C1-C2 alkoxy. 10

[0018] The substituent on the amino group of the present application can be selected from halogen, C1-C5 alkoxy, or C6-C10 phenyl; preferably, halogen, C1-C5 alkoxy, C6-C10 phenyl; more preferably, halogen, C1-C5 alkoxy, C6-C10 phenyl. 10 20 12 ​​​​The substituents on the alkoxy group can be selected from halogen, C1 to C3 alkoxy, phenyl. 10 Alkyl or C6~C 20 Phenyl; preferably selected from halogen, C1~C5 alkyl, C6~C 12 more preferably selected from halogen, C1 to C3 alkyl, phenyl.

[0019] The lipoic acid compound of the present invention is selected from one or more of lipoic acid, lipoamide, and ethyl lipoate; preferably, lipoic acid. According to certain embodiments of the present invention, the lipoic acid compound is lipoic acid; according to other embodiments of the present invention, the lipoic acid compound is lipoamide; according to still other embodiments of the present invention, the lipoic acid compound is ethyl lipoate.

[0020] In the present invention, the amount of 1,3-dienylbenzene is 3 to 6 parts by weight, preferably 4 to 6 parts by weight, and more preferably 4 to 5 parts by weight. According to certain embodiments of the present invention, the amount of 1,3-dienylbenzene is 4 parts by weight.

[0021] The 1,3-dienylbenzene of the present invention is selected from one or more of 1,3-divinylbenzene, 1,3-diisopropenylbenzene, 1,3-di-n-propenylbenzene, 1-vinyl-3-propenylbenzene and 1-propenyl-3-vinylbenzene; preferably, selected from one or more of 1,3-divinylbenzene, 1,3-diisopropenylbenzene and 1,3-di-n-propenylbenzene; more preferably, selected from one or more of 1,3-divinylbenzene and 1,3-diisopropenylbenzene. According to certain embodiments of the present invention, the 1,3-dienylbenzene is 1,3-diisopropenylbenzene.

[0022] In the present invention, the amount of iron halide used is 0.2 to 0.8 parts by weight, preferably 0.3 to 0.7 parts by weight, and more preferably 0.5 to 0.7 parts by weight. According to certain embodiments of the present invention, the amount of iron halide used is 0.6 parts by weight.

[0023] The iron halide of the present invention can be selected from one or more of ferric chloride, ferric bromide, and ferric fluoride; preferably, it is selected from one or more of ferric chloride and ferric bromide; more preferably, it is ferric chloride. The iron halide can be used in the form of a hydrate, for example, ferric chloride hexahydrate.

[0024] In the present invention, the amount of the natural polymer compound is 0.1 to 0.3 parts by weight, preferably 0.15 to 0.25 parts by weight, more preferably 0.2 to 0.25 parts by weight. According to certain embodiments of the present invention, the amount of the natural polymer compound is 0.24 parts by weight.

[0025] The natural polymer compound of the present invention is selected from one or more of starch, cellulose, chitosan, and lignin; preferably, selected from one or more of starch, cellulose, and lignin; more preferably, selected from one or more of cellulose and lignin. According to certain embodiments of the present invention, the natural polymer compound is cellulose. According to other embodiments of the present invention, the natural polymer compound is lignin.

[0026] In the present invention, the amount of epoxidized natural rubber is 20 to 30 parts by weight, preferably 23 to 28 parts by weight, more preferably 24 to 26 parts by weight. According to certain embodiments of the present invention, the amount of epoxidized natural rubber is 25 parts by weight.

[0027] In the present invention, the epoxidation degree of the epoxidized natural rubber is 25 to 55%, preferably 35 to 45%, and more preferably 40 to 45%.

[0028] In the present invention, the amount of the carboxyphenyl borate derivative is 1 to 5 parts by weight, preferably 2 to 4 parts by weight, more preferably 2.5 to 3.5 parts by weight. According to certain embodiments of the present invention, the amount of the carboxyphenyl borate derivative is 3 parts by weight.

[0029] The structure of the carboxylphenyl borate derivative of the present invention is shown in formula (II):

[0030]

[0031] In formula (II), R1 is selected from hydrogen, halogen, C1-C 10 alkyl; preferably, selected from hydrogen, halogen, and C1-C5 alkyl; more preferably, selected from hydrogen, halogen, and C1-C3 alkyl. According to certain embodiments of the present invention, R1 is hydrogen, and in other embodiments, R1 is fluorine. Examples of halogen include, but are not limited to, F, Cl, Br, and I. Examples of alkyl include, but are not limited to, methyl, ethyl, propyl, and butyl.

[0032] In the present invention, the derivative of carboxyphenyl borate is selected from one or more of 4-carboxyphenyl borate pinacol, 4-carboxy-2-fluorophenyl borate pinacol, 4-carboxy-2-chlorophenyl borate pinacol, 4-carboxy-2-bromophenyl borate pinacol, 4-carboxy-2-methylphenyl borate pinacol, and 4-carboxy-2-ethylphenyl borate pinacol; preferably, it is selected from one or more of 4-carboxyphenyl borate pinacol and 4-carboxy-2-fluorophenyl borate pinacol; more preferably, it is 4-carboxyphenyl borate pinacol.

[0033] In the present application, the amount of 1,2-dialkylimidazole is 0.5 to 2 parts by weight, preferably 0.5 to 1.5 parts by weight, more preferably 0.5 to 1 part by weight. According to certain embodiments of the present application, the amount of 1,2-dialkylimidazole is 1 part by weight.

[0034] The 1,2-dialkylimidazole of the present application is selected from one or more of 1,2-dimethylimidazole, 1,2-diethylimidazole, 1,2-di-n-propylimidazole, 1,2-diisopropylimidazole, and 1,2-dibutylimidazole; preferably, from one or more of 1,2-dimethylimidazole and 1,2-diethylimidazole; more preferably, from 1,2-dimethylimidazole.

[0035] In the present application, the amount of alkylamidoacetic acid is 0.5 to 2 parts by weight, preferably 0.5 to 1.3 parts by weight, more preferably 0.5 to 0.7 parts by weight. According to certain embodiments of the present application, the amount of alkylamidoacetic acid is 0.6 parts by weight.

[0036] The alkylamidoacetic acid of the present application is selected from one or more of N-acetylglycine, N-propionylglycine, N-butyrylglycine, N-valerylglycine; preferably, from one or more of N-acetylglycine and N-propionylglycine; more preferably, N-acetylglycine.

[0037] In the present application, the amount of zinc alkylate is 0.5 to 2 parts by weight, preferably 0.5 to 1.3 parts by weight, more preferably 0.5 to 1 part by weight. According to certain embodiments of the present application, the amount of zinc alkylate is 1 part by weight.

[0038] The zinc alkylate of the present application is selected from one or more of zinc acetate, zinc propionate, zinc butyrate, zinc valerate, and zinc hexanoate; preferably, from one or more of zinc acetate, zinc propionate, and zinc butyrate; more preferably, from one or more of zinc acetate and zinc propionate. According to certain embodiments of the present application, the zinc alkylate is zinc acetate. The zinc alkylate can be used in the form of a hydrate, for example, can be zinc acetate dihydrate.

[0039] According to the asphalt modifier of the present application, preferably, the lipoic acid compound is selected from one or more of lipoic acid, lipoamide and ethyl lipoate; the 1,3-dialkenylbenzene is selected from one or more of 1,3-divinylbenzene, 1,3-diisopropenylbenzene, 1,3-di-n-propenylbenzene, 1-ethenyl-3-propenylbenzene and 1-propenyl-3-ethenylbenzene; the iron halide is selected from one or more of ferric chloride, ferric bromide and ferric fluoride; the carboxyphenylboronic acid ester derivative is selected from one or more of 4-carboxyphenylboronic acid pinacol ester, 4-carboxy-2-fluorophenylboronic acid pinacol ester, 4-carboxy-2-chlorophenylboronic acid pinacol ester, 4-carboxy-2-bromophenylboronic acid pinacol ester, 4-carboxy-2-methylphenylboronic acid pinacol ester and 4-carboxy-2-ethylphenylboronic acid pinacol ester; the 1,2-dialkylimidazole is selected from one or more of 1,2-dimethylimidazole, 1,2-diethylimidazole, 1,2-di-n-propylimidazole, 1,2-diisopropenylimidazole and 1,2-dibutylimidazole; the alkylamidoacetic acid is selected from one or more of N-acetylglycine, N-propionylglycine, N-butyrylglycine and N-valerylglycine; and the zinc alkylate is selected from one or more of zinc acetate, zinc propionate, zinc butyrate, zinc valerate and zinc hexanoate.

[0040] According to the asphalt modifier of the present application, preferably, in formula (I), R is selected from substituted or unsubstituted amino, hydroxyl or C1-C5 alkoxy; and in formula (II), R1 is selected from hydrogen, halogen or C1-C5 alkyl. Further preferably, R is selected from unsubstituted amino, hydroxyl or C1-C2 alkoxy. Examples of C1-C2 alkoxy include, but are not limited to, methoxy or ethoxy. R1 is selected from hydrogen, halogen or C1-C3 alkyl. Examples of C1-C3 alkyl include, but are not limited to, methyl, ethyl or isopropyl.

[0041] According to the asphalt modifier of the present application, preferably, the asphalt modifier is composed of a soft phase and a hard phase.

[0042] The soft phase of the present application provides abundant hydrogen bonds (secondary hydroxyl, carboxylic hydroxyl), and the hard phase has hydrogen bond acceptors (epoxy, ester carbonyl), so that a cross-linking system is formed through hydrogen bond interface to realize self-assembly of the two phases in molten asphalt.

[0043] In another aspect, the present application provides a preparation method of the asphalt modifier, comprising the following steps:

[0044] (1) heating the lipoic acid compound to melt under stirring until it becomes a yellow transparent liquid; then adding 1,3-dialkenylbenzene dropwise to obtain a cross-linked polymer; adding the iron halide and the natural high molecular compound into the cross-linked polymer to stir and obtain a mixed melt; cooling the melt to room temperature to obtain a soft phase;

[0045] (2) plasticating the epoxidized natural rubber in an internal mixer; then adding a derivative of carboxyphenylboronic acid, 1,2-dialkylimidazole, alkylamidoacetic acid and zinc alkylate into the internal mixer to mix, to obtain a mixture; placing the mixture at 40-75℃ for 12-48h, and then performing hot-pressing treatment on the mixture by using a flat vulcanizing machine;

[0046] The product obtained after hot-pressing treatment of the mixture by using a flat vulcanizing machine is subjected to powdering treatment by using a liquid nitrogen refrigeration pulverization technology, to obtain a hard phase.

[0047] According to the preparation method of the present application, preferably, in step (1), the lipoic acid compound is heated to melt under stirring at a rotating speed of 150-300r / min, 1,3-dialkenylbenzene is added dropwise, and the reaction is performed for 1-3h to obtain a crosslinked polymer; in step (2), the rotating speed of the internal mixer is 30-60r / min, the plasticating temperature is 30-75℃, the plasticating time is 10-30min, the vulcanizing temperature of the flat vulcanizing machine is 150-200℃, the vulcanizing time is 8-15min, and the vulcanizing pressure is 5-20MPa; liquid nitrogen is introduced into the pulverizer to maintain the temperature at-50℃ to-30℃, to obtain a hard phase; the average particle size of the hard phase is 50-150μm.

[0048] In step (1), the lipoic acid compound is heated to melt under stirring at a rotating speed of 150-300r / min; preferably, the lipoic acid compound is heated to melt under stirring at a rotating speed of 180-280r / min; more preferably, the lipoic acid compound is heated to melt under stirring at a rotating speed of 150-230r / min. The heating temperature can be 100-160℃; preferably, 110-130℃.

[0049] The reaction is performed for 1-3h after dropwise addition of 1,3-dialkenylbenzene to obtain a crosslinked polymer; preferably, the reaction is performed for 1-2.5h after dropwise addition of 1,3-dialkenylbenzene to obtain a crosslinked polymer; more preferably, the reaction is performed for 1-2h after dropwise addition of 1,3-dialkenylbenzene to obtain a crosslinked polymer.

[0050] According to some embodiments of the present application, the lipoic acid compound is heated to melt under stirring at a temperature of 120℃ and a rotating speed of 200r / min, the reaction is performed for 1.5h after dropwise addition of 1,3-dialkenylbenzene to obtain a crosslinked polymer.

[0051] The halogenated iron and the natural high molecular compound are added to the crosslinked polymer and stirred for 1-10min; preferably, 3-8min, more preferably, 4-6min.

[0052] In step (2), the epoxidized natural rubber is plasticated for 10-30 min, preferably 10-20 min, more preferably 10-15 min at a rotation speed of 30-60 r / min, preferably 35-55 r / min, more preferably 35-45 r / min, and a plasticating temperature of 30-75 °C, preferably 30-45 °C, more preferably 30-35 °C in a mixer.

[0053] According to some embodiments of the present application, the epoxidized natural rubber is plasticated for 15 min at a rotation speed of 40 r / min and a plasticating temperature of 30 °C in a mixer.

[0054] After adding the derivative of carboxyphenyl borate, 1,2-dialkyl imidazole, alkyl amido acetic acid and zinc alkyl acid, the mixture is obtained by mixing for 5-30 min, preferably 10-20 min, at a rotation speed of 30-60 r / min, preferably 35-55 r / min, more preferably 45-55 r / min, and a temperature of 40-80 °C, preferably 50-70 °C in a mixer.

[0055] According to some embodiments of the present application, after adding the derivative of carboxyphenyl borate, 1,2-dialkyl imidazole, alkyl amido acetic acid and zinc alkyl acid, the mixture is obtained by mixing for 15 min at a rotation speed of 50 r / min and a plasticating temperature of 60 °C in a mixer.

[0056] The curing temperature of the flat curing press is 150-200 °C, preferably 170-190 °C, more preferably 175-185 °C. The curing time is 8-15 min, preferably 10-15 min, more preferably 10-13 min. The curing pressure is 5-20 MPa, preferably 5-15 MPa, more preferably 8-13 MPa.

[0057] According to some embodiments of the present application, the curing temperature of the flat curing press is 180 °C, the curing time is 10 min, and the curing pressure is 10 MPa.

[0058] Liquid nitrogen is introduced into the pulverizer to maintain a temperature of -50 °C to -30 °C, preferably -45 °C to -35 °C, more preferably -40 °C to -35 °C. The average particle size of the hard phase is 50-150 μm. Preferably, it is 70-120 μm, more preferably 90-110 μm.

[0059] According to some embodiments of the present application, liquid nitrogen is introduced into the pulverizer to maintain a temperature of -40 °C to obtain a hard phase. The average particle size of the hard phase is 100 μm.

[0060] In yet another aspect, the present application provides use of the asphalt modifier according to the present application in improving at least one of the following properties of asphalt: (A) self-repairing property; (B) rut resistance; (C) crack resistance.

[0061] The present application finds that the asphalt molecule surface has active functional groups such as carboxyl and amine groups, which can form stable interfacial action with the active sites of the soft phase carboxyl, hydroxyl, disulfide bond in the modifier and the hard phase epoxy, ester carbonyl, etc., ensuring good compatibility of the asphalt and the modifier and improving the self-repairing property, high-temperature rut resistance and low-temperature crack resistance of the asphalt.

[0062] The rut resistance refers to the rut resistance under high-temperature conditions. High temperature refers to a temperature of 60-75°C; preferably 64-70°C.

[0063] The crack resistance refers to the crack resistance under low-temperature conditions. Low temperature refers to a temperature of -25 to -10°C; preferably -20 to -15°C. The crack resistance can be characterized by the creep rate and / or the creep stiffness.

[0064] In yet another aspect, the present application provides a self-repairing asphalt, which comprises the asphalt and the asphalt modifier according to the present application. Based on 100 parts by weight of the base asphalt, the self-repairing asphalt comprises 6-20 parts by weight of the asphalt modifier.

[0065] In the present application, based on 100 parts by weight of the base asphalt, the soft phase in the asphalt modifier can be used in an amount of 3-10 parts by weight, preferably 5-10 parts by weight, for example, 5 parts by weight or 10 parts by weight. Based on 100 parts by weight of the base asphalt, the hard phase in the asphalt modifier can be 3-10 parts by weight, preferably 5-10 parts by weight, for example, 5 parts by weight or 10 parts by weight.

[0066] According to some embodiments of the present application, the self-repairing asphalt comprises 100 parts by weight of the base asphalt, 5 parts by weight of the soft phase and 5 parts by weight of the hard phase. According to other embodiments of the present application, the self-repairing asphalt comprises 100 parts by weight of the base asphalt, 10 parts by weight of the soft phase and 5 parts by weight of the hard phase. According to still other embodiments of the present application, the self-repairing asphalt comprises 100 parts by weight of the base asphalt, 5 parts by weight of the soft phase and 10 parts by weight of the hard phase.

[0067] In yet another aspect, the present application provides a method for preparing the self-repairing asphalt according to the present application, which comprises the following steps: heating the base asphalt to be molten, adding the hard phase, shearing with a high-speed shearing emulsifier for 0.5-3 h to obtain an asphalt mixture; adding the soft phase to the asphalt mixture and stirring to obtain the self-repairing asphalt.

[0068] In the present application, the high-speed shearing emulsifier shearing time is 0.5-3h, preferably 0.5-2h, more preferably 0.5-1.5h. According to some embodiments of the present application, the high-speed shearing emulsifier shearing time is 1h.

[0069] According to the preparation method of the present application, preferably, the matrix asphalt is heated to 120-145℃ to melt the matrix asphalt; the high-speed shearing emulsifier is sheared at a shearing temperature of 140-170℃ and a shearing speed of 3000-7000r / min for 1-3h; the soft phase is added to the asphalt mixture and stirred at a temperature of 120-150℃ and a stirring speed of 400-1000r / min for 5-20min.

[0070] In the present application, the heating temperature of the matrix asphalt can be 120-145℃, preferably 130-135℃, for example, it can be 135℃.

[0071] The high-speed shearing emulsifier shearing temperature can be 140-170℃, preferably 150-160℃, for example, it can be 150℃.

[0072] The shearing speed can be 3000-7000r / min, preferably 4000-6000r / min, for example, it can be 5000r / min.

[0073] The shearing time is 1-3h, preferably 1-1.5h, for example, it can be 1h.

[0074] The heating temperature for adding the soft phase to the asphalt mixture can be 120-150℃, preferably 125-135℃, for example, it can be 130℃. The stirring speed can be 400-1000r / min, preferably 450-650r / min, for example, it can be 500r / min. The stirring time can be 5-20min, preferably 8-15min, for example, it can be 10min.

[0075] The asphalt modifier provided by the present application realizes self-assembly of two phases in molten asphalt through reasonable hydrogen bond interface design, and ensures good compatibility. Through the synergistic effect of the two phases, the low-temperature toughness and self-repairing performance of asphalt are realized, and the anti-rutting performance under high-temperature service is also considered. In addition, the raw materials of the two phases are mainly renewable resources and biological derivative materials, which reduces the consumption of petroleum-based resin materials, meets the performance requirements of road materials under heavy traffic conditions, and meets the design requirements of "low carbon, environmental protection, green and sustainable" pavement materials. DETAILED DESCRIPTION

[0076] The present application will be further described below in conjunction with specific examples, but the scope of protection of the present application is not limited thereto.

[0077] Raw material source description and test method:

[0078]

[0079] The road base asphalt is SK70# road petroleum asphalt of South Korea, and the basic performance indexes thereof are tested according to the Test Regulation of Highway Engineering Asphalt and Asphalt Mixture (JTG E20-2011), and the test results are as follows:

[0080] Technical specifications Test results Technical requirements Test method Penetration (25°C, 100 g, 5 s, 0.1 mm) 70.4 60~80 T-0604-2011 Softening point (°C) 48.2 ≥45 T0606-2011 Ductility (10°C, cm) 35.2 ≥20 T-0605-2011 Density (10°C, g / cm 3 )]]> 1.023 - T-0603-2011 RTFOT mass loss (%) 0.06 <±0.8 T-0610-2011

[0081] Preparation of asphalt modifier of Example 1

[0082] (1) Preparation of the soft phase:

[0083] 16 parts by weight of lipoic acid was placed in a three-necked flask and heated at a temperature of 120°C and a rotation speed of 200 r / min until it became a yellow transparent liquid; then 4 parts by weight of 1,3-diisopropenylbenzene was slowly added dropwise into the flask, and the reaction was continued for 1.5 h. 0.6 parts by weight of iron trichloride hexahydrate and 0.24 parts by weight of cellulose were added into the three-necked flask and reacted for 5 min to obtain a mixed melt. The mixed melt was poured into a mold and cooled to room temperature to obtain the soft phase PLA.

[0084] (2) Preparation of the hard phase:

[0085] 25 parts by weight of epoxidized natural rubber was plasticized in an internal mixer at a temperature of 30°C and a rotation speed of 40 r / min for 15 min; then 3 parts by weight of 4-carboxyphenylboronic pinacol ester, 1 part by weight of 1,2-dimethylimidazole, 0.6 parts by weight of N-acetylglycine and 1 part by weight of zinc diacetate were added into the internal mixer and mixed at a temperature of 60°C and a rotation speed of 50 r / min for 15 min to obtain a mixture. The mixture was placed at room temperature for 24 h and then loaded into a flat vulcanizing machine mold and vulcanized at a temperature of 180°C and a pressure of 10 MPa for 10 min to obtain a product.

[0086] The product obtained after the hot pressing treatment by the flat vulcanizing machine was powdered by using the liquid nitrogen freezing and crushing technology. Liquid nitrogen was introduced into the pulverizer, and the temperature was maintained at -40°C. After crushing, the hard phase (average particle size of 100 μm) was obtained, which was recorded as PENR.

[0087] Preparation of self-repairing asphalt of Application Example 1

[0088] 100 parts by weight of base asphalt was heated to 135℃ to melt, then 5 parts by weight of PENR was added, and a high-speed shearing emulsifier was used to shear at a temperature of 150℃ and a shearing speed of 5000r / min for 1h to obtain an asphalt mixture. 5 parts by weight of PLA was added to the asphalt mixture, and stirred at a temperature of 130℃ and a stirring speed of 500r / min for 10min, and then cooled to room temperature to obtain a self-repairing asphalt, which was named as 5-PENR&5-PLA.

[0089] Application Example 2

[0090] The difference from application example 1 is only that 5 parts by weight of PENR and 5 parts by weight of PLA are replaced by 5 parts by weight of PENR and 10 parts by weight of PLA. A self-repairing asphalt is prepared and named as 5-PENR&10-PLA.

[0091] Application Example 3

[0092] The difference from application example 1 is only that 5 parts by weight of PENR and 5 parts by weight of PLA are replaced by 10 parts by weight of PENR and 5 parts by weight of PLA. A self-repairing asphalt is prepared and named as 10-PENR&5-PLA.

[0093] The self-repairing ability of base asphalt and the self-repairing asphalt of application examples 1-3 was verified. The self-repairing performance of base asphalt and the self-repairing asphalt prepared in application examples 1-3 was verified by using a cutting repair test. The specific method is as follows: a mold was used to preform a sample strip of asphalt, and the mold was as described in T0605-2011 asphalt ductility test section 2.2 of “Highway Engineering Asphalt and Asphalt Mixture Test Procedures” (JTG E20-2011) and 2.3 section of the mold bottom plate. A 10mm long and 3.3mm deep cut was made in the middle of the sample strip, and then the sample strip was placed at 25℃ for 6h to obtain the self-repaired asphalt.

[0094] The self-repairing efficiency of base asphalt (SK70) and the self-repairing asphalt of application examples 1-3 is shown in Table 1.

[0095] The self-repairing efficiency was calculated by the following formula:

[0096] Self-repairing efficiency % = ductility of self-repaired asphalt (mm) / ductility of original sample asphalt (mm) x 100%.

[0097] Table 1

[0098] No. SK70 Application Example 1 Application Example 2 Application Example 3 Self-repairing efficiency / % 19.4 65.3 78.3 62.7

[0099] As shown in Table 1, the asphalt modifier significantly improves the self-repairing performance of the asphalt, and the self-repairing performance of the asphalt is enhanced with the increase of the soft phase (PLA) addition amount. When 10 wt% of the soft phase (PLA) is added, the self-repairing efficiency of the asphalt is enhanced by 58.9% relative to the matrix asphalt SK70. The self-repairing asphalt of the present application has good self-repairing performance.

[0100] According to the Highway Engineering Asphalt and Asphalt Mixture Test Regulation (JTG E20-2011), the rheological property test of the matrix asphalt and the self-repairing asphalt of application examples 1-3 is carried out by T0628-2011, and the test results are shown in Table 2.

[0101] Table 2

[0102]

[0103] As shown in Table 2, the asphalt modifier of the present application significantly improves the high-temperature rut resistance of the asphalt, and the high-temperature rut resistance of the self-repairing asphalt is enhanced with the increase of the hard phase (PENR) addition amount. Among them, the rut resistance factor (G* / sinδ) of the self-repairing asphalt with the ratio of 10-PENR&5-PLA at 64℃ is increased by 94% compared with the matrix asphalt SK70.

[0104] According to the Highway Engineering Asphalt and Asphalt Mixture Test Regulation (JTG E20-2011), the bending creep stiffness (S) test of the matrix asphalt and the self-repairing asphalt of application examples 1-3 is carried out by T0627-2011 at-18℃. The test results are shown in Table 3.

[0105] Table 3

[0106] No. SK70 Application Example 1 Application Example 2 Application Example 3 S / MPa 124.2 87.4 73.7 112.6 m 0.27 0.41 0.43 0.36

[0107] As shown in Table 3, the asphalt modifier of the present application can improve the low-temperature crack resistance of the asphalt. Among them, the creep rate (m) of the self-repairing asphalt with the ratio of 5-PENR&10-PLA is increased by 53.6% compared with the matrix asphalt SK70.

[0108] In summary, the asphalt modifier of the present application can realize the synergistic improvement of the self-repairing performance, high-temperature deformation resistance and low-temperature crack resistance of the asphalt, and the modifier of the present application endows the asphalt with excellent high and low temperature performance.

[0109] The present application is not limited to the above-mentioned embodiments, and any modification, improvement and replacement that can be thought of by those skilled in the art without departing from the essential content of the present application falls within the scope of the present application.

Claims

1. An asphalt modifier, characterized in that: The asphalt modifier includes a soft phase and a hard phase; The soft phase is prepared from raw materials including the following components: The thioctic acid compound is as shown in formula (I): In formula (I), R is selected from substituted or unsubstituted amino, hydroxyl, substituted or unsubstituted C1-C 10 Alkyl group; the natural polymer compound is selected from one or more of starch, cellulose, chitosan and lignin; The hard phase is prepared from raw materials including the following components: The epoxidation degree of the epoxidized natural rubber is 25-55%, and the structure of the derivative of the carboxylphenyl borate ester is shown in formula (II): In formula (II), R1 is selected from hydrogen, halogen, C1-C 10 of alkyl.

2. The asphalt modifier according to claim 1, characterized in that The lipoic acid compound is selected from one or more of lipoic acid, lipoamide and ethyl lipoate; The 1,3-dienylbenzene is selected from one or more of 1,3-divinylbenzene, 1,3-diisopropenylbenzene, 1,3-di-n-propenylbenzene, 1-vinyl-3-propenylbenzene and 1-propenyl-3-vinylbenzene; The iron halide is selected from one or more of ferric chloride, ferric bromide and ferric fluoride; The derivative of the carboxyphenyl borate is selected from one or more of 4-carboxyphenyl boric acid pinacol ester, 4-carboxy-2-fluorophenyl boric acid pinacol ester, 4-carboxy-2-chlorophenyl boric acid pinacol ester, 4-carboxy-2-bromophenyl boric acid pinacol ester, 4-carboxy-2-methylphenyl boric acid pinacol ester and 4-carboxy-2-ethylphenyl boric acid pinacol ester; The 1,2-dialkylimidazole is selected from one or more of 1,2-dimethylimidazole, 1,2-diethylimidazole, 1,2-di-n-propylimidazole, 1,2-diisopropenylimidazole and 1,2-dibutylimidazole; The alkyl amidoacetic acid is selected from one or more of N-acetylglycine, N-propionylglycine, N-butyrylglycine and N-valerylglycine; The alkyl zinc acid is selected from one or more of zinc acetate, zinc propionate, zinc butyrate, zinc valerate and zinc hexanoate.

3. The asphalt modifier according to claim 1, characterized in that R is selected from substituted or unsubstituted amino, hydroxy or C1-C5 alkoxy, and R1 is selected from hydrogen, halogen, and C1-C5 alkyl.

4. The asphalt modifier according to claim 1, characterized in that The asphalt modifier consists of a soft phase and a hard phase.

5. The method for preparing an asphalt modifier according to claim 1, wherein: The steps include: (1) heating a lipoic acid compound to melt under stirring until it becomes a yellow transparent liquid; then adding 1,3-dienylbenzene dropwise to obtain a cross-linked polymer; adding an iron halide and a natural polymer compound to the cross-linked polymer and stirring to obtain a mixed melt; cooling the melt to room temperature to obtain a soft phase; (2) masticating the epoxidized natural rubber in an internal mixer; then adding a carboxyphenyl borate derivative, 1,2-dialkylimidazole, alkylamide acetic acid, and alkyl acid zinc into the internal mixer and mixing to obtain a mixture; placing the mixture at 40 to 75° C. for 12 to 48 hours, and then hot pressing the mixture using a flat vulcanizer; The mixture is subjected to hot pressing treatment on a flat vulcanizing machine, and the obtained product is powdered using liquid nitrogen freezing and crushing technology to obtain a hard phase.

6. The preparation method according to claim 5, characterized in that: In step (1), the lipoic acid compound is heated to melt under stirring conditions at a rotation speed of 150 to 300 r / min, 1,3-dienylbenzene is added dropwise, and the mixture is reacted for 1 to 3 hours to obtain a cross-linked polymer; In step (2), the speed of the internal mixer is 30-60 r / min, the plasticizing temperature is 30-75° C., the plasticizing time is 10-30 min, the vulcanizing temperature of the flat vulcanizing press is 150-200° C., the vulcanizing time is 8-15 min, and the vulcanizing pressure is 5-20 MPa; Liquid nitrogen is introduced into the pulverizer to maintain the temperature at -50°C to -30°C to obtain a hard phase; the average particle size of the hard phase is 50 to 150 μm.

7. Use of the asphalt modifier according to any one of claims 1 to 4 or the asphalt modifier obtained by the preparation method according to any one of claims 5 or 6 for improving at least one of the following properties of asphalt: (A) Self-repair performance; (B) Anti-rutting performance; (C) Crack resistance.

8. A self-repairing asphalt, characterized in that: The self-repairing asphalt comprises asphalt and the asphalt modifier according to any one of claims 1 to 4.

9. The method for preparing self-repairing asphalt according to claim 8, characterized in that: The steps include: After the base asphalt is heated to melt, the hard phase is added and sheared for 0.5 to 3 hours using a high-speed shear emulsifier to obtain an asphalt mixture; the soft phase is added to the asphalt mixture and stirred to obtain self-repairing asphalt.

10. The preparation method according to claim 9, characterized in that Heat the matrix asphalt to 120-145°C to melt the matrix asphalt; The high-speed shear emulsifier is used for shearing for 1 to 3 hours at a shear temperature of 140 to 170°C and a shear speed of 3000 to 7000 r / min; The soft phase is added to the asphalt mixture and stirred at a temperature of 120 to 150° C. and a stirring speed of 400 to 1000 r / min for 5 to 20 minutes.